The effect of entrepreneurship management in research and development in the engineering faculty in Malaysia / Azlina Idris … [et al.] - Idris, Azlina; Sarnin, Suzi Seroja; Naim, Nani Fadzlina; Abdullah, Wan Fazlida Hanim (Universiti Teknologi MARA, Shah Alam: Faculty of Law, 2018)
In the era of globalization, education should be enhanced to achieve the vision of developed nation and highly educated people. Entrepreneurship education should also be applied especially in higher learning education to ensure students are more competitive in the workplace. This is also to ensure students are more independent and have the potential to open their own business rather than working with others. Hence, the Faculty of Electrical Engineering, UiTM, Malaysia has taken the step by providing opportunities for students and lecturers in exposing the entrepreneurial learning directly or indirectly. In this paper, the methods employed by the faculty in encouraging entrepreneurship education among students have been discussed. The effect of the new educational system that has been implemented has also been analyzed. It is found that this method has greatly improved the performance of the staff and the students especially in their career path.